Analysis of autonomic nervous function and associated symptoms in patients with peripheral vestibular disorders - Wang, Chuangwei; Zhang, Sai; Xie, Peifan; Lang, Yilin; Hao, Yongci; Wang, Wenting; Gu, Ping (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to investigate the differential effects of vestibular lesion sites, specifically the semicircular canals and otolith organs, on autonomic nervous system function, emotional state, and sleep quality by analyzing heart rate variability (HRV) and clinical symptom scale scores in patients with peripheral vestibular disorders.MethodsA total of 144 patients with peripheral vestibular disorders admitted between September 2023 and December 2024 were enrolled and divided into four groups based on vestibular function test results: Group A (normal semicircular canal and otolith function), Group B (abnormal otolith function), Group C (abnormal semicircular canal function), and Group D (abnormal semicircular canal and otolith function). Baseline characteristics, clinical symptoms, sleep and emotion scale scores, and HRV parameters were compared across groups.ResultsSignificant differences were observed in the Dizziness Handicap Inventory (DHI) total score, DHI physical and functional sub-scores, Pittsburgh Sleep Quality Index score, and HRV across the four groups (all p < 0.05). Standard deviation of NN intervals (SDNN) was negatively correlated with age, DHI, Hamilton Depression Rating Scale scores, and corrected QT interval (all p < 0.05). DHI was identified as an independent risk factor for reduced SDNN (p < 0.05).ConclusionMultisite vestibular lesions significantly exacerbated functional impairment and autonomic dysfunction, underscoring the need for an integrated assessment of vestibular function, emotional state, and sleep quality for clinical management.